TNF-alpha, H2O2 and NO response of peritoneal macrophages to Yersinia enterocolitica O : 3 derivatives - Carlos, Iracilda Zeppone [UNESP]; Monnazzi, LGS; Falcao, D. P.; de Medeiros, BMM (Elsevier B.V., 2004)
In this study, the effect of Yersinia derivatives on nitric oxide (NO), hydrogen peroxide (H2O2) and tumor necrosis factor-alpha (TNF-alpha) production by murine peritoneal macrophages was investigated. Addition of lipopolysaccharide (LPS) to the macrophage culture resulted in NO production that was dose dependent. on the other hand, bacterial cellular extract (CE) and Yersinia outer proteins (Yops) had no effect on NO production. The possible inhibitory effect of Yops on macrophage cultures stimulated with LPS was investigated. Yops partially inhibited NO production (67.4%) when compared with aminoguanidine. The effects of Yersinia derivatives on H2O2 production by macrophages were similar to those on NO production. LPS was the only derivative that stimulated H2O2 release in a dose-dependent manner. All Yersinia derivatives provoked the production of TNF-alpha, but LPS had the strongest effect, as observed for NO production. CE and Yops stimulated TNF-alpha production to a lesser extent than LPS. The results indicate the possibility that in vivo Yops may aid the evasion of the bacteria from the host defense mechanism by impairing the secretion of NO by macrophages. (C) 2003 Elsevier SAS. All rights reserved.
Keywords: Yersinia enterocolitica; macrophages; nitric oxide; hydrogen peroxide; TNF-alpha